Investigation of the Antifouling Properties of Phenyl Phosphorylcholine-Based Modified Gold Surfaces - Parviz, M.; Darwish, Nadim; Alam, M.; Parker, S.; Ciampi, S.; Gooding, J. (Wiley - VCH Verlag GmbH & Co. KGaA, 2014)
Low impedance, antifouling coatings on gold electrodes based on three new zwitterionic phenyl phosphorylcholine (PPC)-based layers namely 1) reductively adsorbed PPC diazonium salt, 2) dithiocarbamate PPC SAM and 3) lipoamide PPC SAM (PPC coupled to a-lipoic acid) were evaluated. The layers were assessed for their ability to limit nonspecific adsorption of proteins to electrode surface with some significant differences observed compared with previously studied PPC diazonium salts reductively adsorbed on glassy carbon. Fluorescence microscopy and electrochemical impedance spectroscopy results suggest that protein adsorption is sensitive to the difference in the structure of the PPC molecules and the charge neutrality of the layers. The lipoamide PPC SAM was shown to be the most effective at resisting nonspecific protein adsorption and this layer was as effective as the 'gold standard' of oligo(ethylene oxide) SAMs on gold and PPC diazonium salts reductively adsorbed on glassy carbon.